Optimization of Digital Branding and Marketing for Gempol MSMEs Through WhatsApp Business: Optimalisasi Digital Branding dan Marketing pada UMKM Gempol Melalui WhatsApp Business - Meylianingrum, Kurniawati; El Fahmi , Elok Fa`iz Fatma; Jaya, Tiara Juliana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The number of competitors is the main factor for entrepreneurs to enter the world of very tight competition. The right marketing and media strategies are used to reach the intended market so that the sales volume of these entrepreneurs always increases and makes a profit. The impact of information technology can develop aspects of entrepreneurial capabilities, and industrial ways to survive have developed in line with the creative economy paradigm, where innovative, proactive and risk-taking aspects are not enough in the context of the knowledge economy. This service is based on community development. The output obtained is the understanding of business actors about digital marketing. This community service's outcome is installing the WhatsApp business application and its use in marketing MSME products. The importance of using WhatsApp business features include automatic message replying features, can management of business profiles, and provide a product catalogue owned by MSMEs.